An Invitro Study on The Damage of Cell Membrane by Silica Oxide Nanoparticles - Elham Yektadoost; Farnoosh Attar; Soyar Sari; Mojtaba Falahati (Islamic Azad University, 2016)
Nowadays, growing interest in the application of nanotechnology in biomedical and biotechnological fields has opened a new avenue to explore the nanoparticles-biological system interaction. Indeed, a clear gap is still in the cytotoxic effect of NPs on the biological systems. For this purpose, the interaction of the silica oxide nanoparticles (SiO2-NP) with the PC12 cell line, as a model of nervous system cell line, was examined by lactate dehydrogenase (LDH) assay. For LDH assay, PC12 cells were treated with varying concentration of SiO2-NP up to 100 μg/ml and all assays were conducted at 48h after SiO2-NP incubation. The results showed that the cytotoxicity of SiO2-NP approached to its highest level after 48 h. It was also revealed that as the concentration of SiO2-NP increases to higher amounts, the LDH absorbance enhances. Finally, it may be suggested that several factors such as nanoparticle concentration and exposure time could influence the type of interaction between NPs and the biological system. Thus, the type of interaction and cytotoxic effects of NPs can be mediated by considering these factors.